2013
DOI: 10.3171/2013.3.spine12923
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous center of rotation behavior of the lumbar spine with ligament failure

Abstract: Object The goal of this study was to investigate the effect of ligament failure on the instantaneous center of rotation (ICR) in the lower lumbar spine. Methods A 3D finite element model of the L4–5 segment was obtained and validated. Ligament failure was simulated by reducing ligaments in a stepwise manner from posterior to anterior. A pure bending moment of 7.5 Nm was applied to the model in 3 anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…Though, this relationship was quite muted for the lateral bending direction. Previous studies have investigated the role of ligament failure on a single L4-L5 spinal unit and similarly reported an increase in motion with loss of surrounding stabilizing structures 12,13 . Each of these studies observed a larger response in the lateral bending direction than reported herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, this relationship was quite muted for the lateral bending direction. Previous studies have investigated the role of ligament failure on a single L4-L5 spinal unit and similarly reported an increase in motion with loss of surrounding stabilizing structures 12,13 . Each of these studies observed a larger response in the lateral bending direction than reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…Disc degeneration has been the subject of many lumbar FE models 911 , however very few studies have investigated the role of ligamentous pathology or failure 12,13 . Moreover, these studies only included a single spinal unit, rather than a longer spinal segment.…”
Section: Introductionmentioning
confidence: 99%
“…However, bone strength varies greatly between individuals as a result of the effect of osteoporosis, and this has been difficult to reproduce. Almost all previous studies have used a two-layer model of bone material consisting of cortical bone and medulla with consistent mechanical properties for analysis [10,12,13]. In this study, we created a patient-specific FE model using bone densities derived from CT images of an individual patient, for which we determined element-specific Young's modulus and carried out damage analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we created a patient-specific FE model using bone densities derived from CT images of an individual patient, for which we determined element-specific Young's modulus and carried out damage analysis. Although most researchers have found it difficult to establish a model for the ligaments around the vertebral bodies, modeling them only as spring elements exerting tension only in one dimension [13,23], we modeled and analyzed the ligaments around the vertebral bodies as three-dimensional finite elements in this study. To the best of our knowledge, we are the first to successfully reproduce the tension and deformation behavior around the cages used in PLIF in a simulation using the osteoporotic vertebral bodies of an old person, allowing us to predict the mechanism by which cage subsidence occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation